Marching Ahead through the Pandemic: Continuing Anesthesia Services in COVID Era—Our Experience from a Tertiary Care Cancer Centre - Bhan, Swati; Gupta, Raghav; Vig, Saurabh; Garg, Rakesh; Gupta, Nishkarsh; Kumar, Vinod; Bharati, Sachidanand Jee; Mishra, Seema; Ratre, Brajesh; Pandit, Anuja; Sirohiya, Prashant; Singh, Ram; Kumar, Balbir; Bhopale, Shweta; Bhatnagar, Sushma (South Asian Journal of Cancer, 2023)
Introduction This paper aims to provide an overview of the administrative and clinical preparations done in a tertiary care cancer hospital in continuing operation theatre (OT) services through the COVID pandemic.Methods Retrospective data collection, data for the past 1.5 years (COVID period) March 2020 to August 2021 were compared to surgical output for a similar duration of time before the COVID era (September 2018–February 2020).Results A total of 1,022 surgeries were done under anesthesia in the COVID period as against 1,710 surgeries done in a similar time frame in the pre-COVID era. Overall, we saw a 40%drop in the total number of cases. Thorax, abdominal, and miscellaneous surgeries (soft tissue sarcomas, urology, and gyneconcology) saw a maximum fall in numbers; however, head and neck cases saw an increase in numbers during the pandemic. Surgical morbidity and mortality were similar in the COVID and pre-COVID era. No cases of severe COVID infection were reported among the healthcare staff working in OT.Discussion We could successfully continue our anesthesia services with minimal risk to healthcare staff throughout the pandemic by adopting major guidelines in a pragmatic and practical approach with minor changes to suit our setup.
Keywords: COVID-19; pandemic; anesthesia; cancer care